2001
DOI: 10.1007/s004640000340
|View full text |Cite
|
Sign up to set email alerts
|

Experience as a factor influencing the indications for laparoscopic colorectal surgery and the results

Abstract: Laparoscopic colorectal surgery is very demanding, and can be performed with low morbidity and mortality rates only by a surgeon with above-average experience with this type of surgery and a large caseload of laparoscopic colorectal procedures. The learning curve for such procedures is appreciably longer than for other laparoscopic operations. With increasing experience, technically more demanding operations, including radical oncologic rectal laparoscopic procedures, can be performed with appreciably reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
0
27

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 24 publications
7
90
0
27
Order By: Relevance
“…Although there were no major differences in perioperative care and patient recovery after elective colonic surgery between European and US patients [22], postoperative length of stay was only 7 days in the United States but 10–13 days in European countries. In Germany, the postoperative hospital stay after colonic cancer surgery is as long as 17 days [24], and even patients undergoing laparoscopic colonic resection remain in hospital for 11–12 days after surgery [25]. Factors other than patient recovery which are responsible for the traditionally prolonged stay in German hospitals include: the reimbursement system hardly ever penalizes postoperative hospital stay; general practitioners are reluctant to treat patients who are discharged early after surgery; many hospitals do not have adequate outpatient facilities to take care of these patients; surgeons fear major complications after discharge (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were no major differences in perioperative care and patient recovery after elective colonic surgery between European and US patients [22], postoperative length of stay was only 7 days in the United States but 10–13 days in European countries. In Germany, the postoperative hospital stay after colonic cancer surgery is as long as 17 days [24], and even patients undergoing laparoscopic colonic resection remain in hospital for 11–12 days after surgery [25]. Factors other than patient recovery which are responsible for the traditionally prolonged stay in German hospitals include: the reimbursement system hardly ever penalizes postoperative hospital stay; general practitioners are reluctant to treat patients who are discharged early after surgery; many hospitals do not have adequate outpatient facilities to take care of these patients; surgeons fear major complications after discharge (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasised that appropriate early conversion can reduce intraoperative complications and postoperative morbidity. 5,52,71 Some have advocated the use of resection-facilitated and handassisted techniques to reduce conversion rates. In a comparative study of laparoscopic versus resectionfacilitated management of complicated diverticulitis, Eijsbouts et al demonstrated improved outcomes with the resection-facilitated approach.…”
Section: Laparoscopic Managementmentioning
confidence: 99%
“…De esta forma, muchas veces un residente es el cirujano principal, pero es guiado por un miembro experimentado del equipo. Marusch et al 19 , en un estudio multicéntrico con más de 1.000 pacientes, cirujanos con más de 100 procedimientos se embarcan en procedimientos más complejos, lo que produce una curva bimodal en el gráfi co de conversión. Así mismo, tampoco, se encontró diferencias entre los primeros 200 casos y el resto de la serie.…”
Section: Discussionunclassified